Neurofilament light chain as a biomarker of meningoencephalitis of unknown etiology in dogs. (10th June 2021) - Yun, Taesik; Koo, Yoonhoi; Chae, Yeon; Lee, Dohee; Kim, Hakhyun; Kim, Soochong; Chang, Dongwoo; Na, Ki‐Jeong; Yang, Mhan‐Pyo; Kang, Byeong‐Teck
Abstract: Background: Neurofilament light chain (NfL) is a neuron‐specific cytoskeletal protein expressed in axons. Damaged axons of the central nervous system release NfLs into the cerebrospinal fluid (CSF) and the blood. In humans with neurologic diseases, NfL is used as a biomarker. Objectives: To identify the potential of NfL as a supportive tool for the diagnosis, prognosis, and monitoring of meningoencephalitis of unknown etiology (MUE) in dogs. Animals: Twenty‐six client‐owned healthy dogs, 10 normal Beagle dogs, and 38 client‐owned MUE dogs. Methods: Cohort study. The concentrations of NfL in serum and CSF were measured using single‐molecule array technology. Results: Median NfL concentration was significantly higher in MUE dogs (serum, 125 pg/mL; CSF, 14 700 pg/mL) than in healthy dogs (serum, 11.8 pg/mL, P  < .0001; CSF, 1410 pg/mL, P  = .0002). The areas under the receiver operating characteristic curves of serum and CSF NfL concentrations were 0.99 and 0.95, respectively. The cut‐off values were 41.5 pg/mL (serum) and 4005 pg/mL (CSF) for differentiating between healthy and MUE dogs, with sensitivities of 89.19% and 90%, respectively, and specificities of 96.97% and 100%, respectively. The NfL concentration showed a significant decrease (pretreatment, 122 pg/mL; posttreatment, 36.6 pg/mL; P  = .02) in the good treatment‐response group and a significant increase (pretreatment, 292.5 pg/mL; posttreatment, 1880 pg/mL, P  = .03) in the poor treatment‐response group. Conclusions and Clinical importance: Neurofilament light chain is a potential biomarker for diagnosing MUE and evaluating response to treatment.